1988
DOI: 10.1002/bit.260310313
|View full text |Cite
|
Sign up to set email alerts
|

Chemical stabilization of glucoamylase from Aspergillus niger against thermal inactivation

Abstract: The applicability of crosslinking an enzyme to an oxidized polysaccharide by reductive alkylation to enhance thermostability has been investigated for glucoamylase from Aspergillus niger. Direct covalent coupling of the enzyme to periodate-oxidized dextran in the presence of NaBH(3)CN results in a conjugate which has thermal properties similar to those of the native enzyme. Our working hypothesis postulates that enhancement of thermostability will result from rigidification of the protein's conformation subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The stabilization of dexOx-Cysteine-modified papaya proteinase was explained by two reasons: firstly, the rigidification of the biocatalyst structure by the crosslinking produced an increased stability; secondly, the enzyme was stabilized by the prevention of protein association via thioldisulfide exchange reaction. In another research effort, glucoamylase from Aspergillus niger was modified with dexOx, trying to get a high crosslinking degree that permitted enhancing the enzyme stability [151]. In order to increase the dexOx crosslinking of the enzyme, it was aminated (aminating both the sugar chains of the protein and the carboxylic residues of the enzyme), promoting a further increase in enzyme stability and activity at high temperatures.…”
Section: Glycosylation Of Enzymes and Promotion Of Intramolecular Cromentioning
confidence: 99%
“…The stabilization of dexOx-Cysteine-modified papaya proteinase was explained by two reasons: firstly, the rigidification of the biocatalyst structure by the crosslinking produced an increased stability; secondly, the enzyme was stabilized by the prevention of protein association via thioldisulfide exchange reaction. In another research effort, glucoamylase from Aspergillus niger was modified with dexOx, trying to get a high crosslinking degree that permitted enhancing the enzyme stability [151]. In order to increase the dexOx crosslinking of the enzyme, it was aminated (aminating both the sugar chains of the protein and the carboxylic residues of the enzyme), promoting a further increase in enzyme stability and activity at high temperatures.…”
Section: Glycosylation Of Enzymes and Promotion Of Intramolecular Cromentioning
confidence: 99%
“…Examples are cited in the following references: urease on phospholipid-bound silica (21), chymotrypsin on aldehyde/agarose gels (22), glucoamylase on various periodateoxidized polysaccharides (23,24), and trypsin on cyanogen bromide activated dextran (25). For example, urease on a phospholipid-coated silica surface showed about 80-90% activity after being treated at 100…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that enzymes possess enhanced thermal stability, when they have been immobilized by covalent attachment to polymers. Examples include glucoamylase on various periodate oxidized polysaccharides (15,16) and trypsin on cyanogen-bromideactivated dextran (12). Other noted effects of protein conjugation to polysaccharides were improved emulsifying properties (17), improved solubility of insoluble gluten (18), enhanced antioxidant effect of ovalbumin (19), and broadened bactericidal effect of lysozyme (20).…”
Section: Introductionmentioning
confidence: 99%